TRANSFORMASI UNIVERSITAS TANJUNGPURA DARI PERGURUAN TINGGI NEGERI BADAN LAYANAN UMUM MENUJU BADAN HUKUM: STRATEGI PADA MASA TRANSISI DALAM ASPEK SUMBER DAYA MANUSIA - Hidayat, Hidayat; Rosnani, Titik; Daud, Ilzar; Sulistiowati, Sulistiowati (Equator Journal of Management and Entrepreneurship (EJME), 2026)
The transformation of Universitas Tanjungpura (Untan) from a Public Service Agency State University (PTN-BLU) to a State University with Legal Entity status (PTN-BH) represents a strategic step aimed at enhancing institutional autonomy, flexibility, and competitiveness. This transition entails fundamental changes in governance, including the management of Human Resources (HR). This journal article examines the challenges and strategies of HR management during the transition period toward PTN-BH status. The study employs a qualitative research method with a case study approach, utilizing document analysis and in-depth interviews with key stakeholders at Universitas Tanjungpura. The findings identify several key challenges: (1) the need to align employment regulations from the BLU framework to the legal entity model, (2) the enhancement of HR competencies to manage expanded institutional autonomy, (3) the transformation of organizational culture toward outcome-oriented performance, and (4) the transition of remuneration and incentive systems toward performance-based schemes. The article proposes several strategic measures, including intensive communication and socialization, the formulation of clear and equitable implementing regulations, comprehensive and sustainable capacity-building programs, and the development of transparent and objective performance appraisal systems. It is concluded that the success of the transition largely depends on the readiness and effective management of human resources. Therefore, HR transition strategies must serve as a fundamental pillar and top priority throughout the entire process of institutional transformation.